Song: To Celia (Verse Version, 2025)
Wentao Zeng’s translation of “To Celia” is an impressive and faithful adaptation that captures both the lyrical beauty and emotional subtleties of Ben Jonson’s original. The translator skillfully preserves the romantic intimacy and delicate imagery, conveying the longing and admiration in a way that resonates in Chinese. The Chinese version maintains the musicality and rhythm of the English original, while carefully rendering idiomatic expressions into elegant, natural phrasing. Notably, elements such as the “rosy wreath” and “kiss in the cup” are translated with sensitivity to both literal and emotional meaning, allowing Chinese readers to experience the imagery vividly. This translation exemplifies a balanced approach: it honors the structure and tone of the original poem while adapting it into fluent, poetic Chinese. The result is a version that is both readable and aesthetically pleasing, demonstrating the translator’s skill in bridging cultural and linguistic contexts without losing the charm of the original.